2020
DOI: 10.7554/elife.57179
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin-mediated membrane fluidity controls peptidoglycan synthesis and MreB movement

Abstract: The bacterial plasma membrane is an important cellular compartment. In recent years it has become obvious that protein complexes and lipids are not uniformly distributed within membranes. Current hypotheses suggest that flotillin proteins are required for the formation of complexes of membrane proteins including cell-wall synthetic proteins. We show here that bacterial flotillins are important factors for membrane fluidity homeostasis. Loss of flotillins leads to a decrease in membrane fluidity that in turn le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 67 publications
(105 reference statements)
1
40
0
Order By: Relevance
“…Next, we wanted to understand the significance of membrane architecture for cell wall synthesis. We perturbed the membrane with benzyl alcohol, a compound that preferentially inserts into disordered membrane regions in vitro ( Muddana et al, 2012 ) and has been used to fluidize membranes from mammalian and bacterial cells ( Friedlander et al, 1987 ; Ingram, 1976 ; Konopásek et al, 2000 ; Nagy et al, 2007 ; Strahl et al, 2014 ; Zielińska et al, 2020 ). In B. subtilis , benzyl alcohol disrupts RIFs ( Müller et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we wanted to understand the significance of membrane architecture for cell wall synthesis. We perturbed the membrane with benzyl alcohol, a compound that preferentially inserts into disordered membrane regions in vitro ( Muddana et al, 2012 ) and has been used to fluidize membranes from mammalian and bacterial cells ( Friedlander et al, 1987 ; Ingram, 1976 ; Konopásek et al, 2000 ; Nagy et al, 2007 ; Strahl et al, 2014 ; Zielińska et al, 2020 ). In B. subtilis , benzyl alcohol disrupts RIFs ( Müller et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 , Table S2). In other work, we observed that some phenotypes associated with peptidoglycan synthesis defects at the septum are not observed when cells are grown on minimal medium [ 30 ]. Therefore, we also analysed the effect of the deletion of PASTA domains in cells grown in a defined minimal medium (SM medium).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a smaller effect on the formation of the Rod complex, but the impact on complex dynamics may be significant in aPLs cells. While this manuscript was under review, it was reported that membrane fluidity controls MreB motion in Bacillus subtilis (Zielińska et al, 2020). Thus, membrane fluidity controls the motion of the Rod complex in both gram-positive and gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 96%